Waking up to the issue! Research inattention and sex-related differences warrant more sleep studies in female athletes - Power, C. J.; Fox, J. L.; Elliott-Sale, K. J.; Bender, A. M.; Dalbo, V. J.; Scanlan, A. T. (Sports Medicine, 2024)
Key Points: